DOWNSTREAMING POLICY ON INDONESIA'S EXPORT VALUE ADDED (CAHIERS MAGELLANES-NS, 2024)
This study examines downstream policies on Indonesia's export value added. The downstream policy, which aims to increase domestic processing of raw materials, has been the focus of the Indonesian government's strategy to improve the competitiveness of the national economy. Using a quantitative approach with descriptive and inferential analysis, this study analyzes Indonesia's export data over a 10-year period (2014-2024). The results show that the implementation of the downstream policy has had a significant positive impact on increasing the added value of exports, especially in the nickel mining sector with an increase in the export value of processed products by more than 200 percent by 2022. This policy has also contributed to the diversification of export products and the creation of new jobs. However, the implementation of the downstream policy still faces several challenges, including limited competent human resources, international trade barriers, and large investment needs. This study concludes that despite the challenges, the downstream policy has proven effective in increasing the value-added of Indonesia's exports and has the potential to drive long-term economic growth. Recommendations to overcome the challenges include improving the quality of human resources, strengthening economic diplomacy, and simplifying regulations.